2013
DOI: 10.1063/1.4793406
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembly of cyclic rod-coil diblock copolymers

Abstract: The phase behavior of cyclic rod-coil diblock copolymer melts is investigated by the dissipative particle dynamics simulation. In order to understand the effect of chain topological architecture better, we also study the linear rod-coil system. The comparison of the calculated phase diagrams between the two rod-coil copolymers reveals that the order-disorder transition point (χN)ODT for cyclic rod-coil diblock copolymers is always higher than that of equivalent linear rod-coil diblocks. In addition, the phase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Considering a side view of a peptidic layer (Figure B), it is observed that the rigid polypeptide backbone aligns perpendicular to the lamellar plane, forming a smectic-like bilayer. This perpendicular organization is a common arrangement found within the rod-like segments of rod–coil and rod–coil–rod block copolymers due to the rods attempting to maximize rod–rod contact (enthalpy driven) while the coils expand to fill the free volume (entropy driven). Furthermore, the bilayer formation, as opposed to interdigitation, is hypothesized to be triggered by the steric bulk of the benzyl-protected side chain and the relatively short polypeptide rod length. At the lamellar interface, the perpendicular peptidic rod packing causes a degree of coil elongation, decreasing the coil flexibility and inhibiting the space-filling ability within a small distance of the coil–rod interface.…”
Section: Resultsmentioning
confidence: 96%
“…Considering a side view of a peptidic layer (Figure B), it is observed that the rigid polypeptide backbone aligns perpendicular to the lamellar plane, forming a smectic-like bilayer. This perpendicular organization is a common arrangement found within the rod-like segments of rod–coil and rod–coil–rod block copolymers due to the rods attempting to maximize rod–rod contact (enthalpy driven) while the coils expand to fill the free volume (entropy driven). Furthermore, the bilayer formation, as opposed to interdigitation, is hypothesized to be triggered by the steric bulk of the benzyl-protected side chain and the relatively short polypeptide rod length. At the lamellar interface, the perpendicular peptidic rod packing causes a degree of coil elongation, decreasing the coil flexibility and inhibiting the space-filling ability within a small distance of the coil–rod interface.…”
Section: Resultsmentioning
confidence: 96%
“…DPD has been successfully applied to simulate a number of soft matter systems: block co-polymers, [22][23][24] colloidal suspensions, 25 lipid bilayers, 26,27 nanoparticles 28,29 and liquid crystalline phases 30,31 including those formed from complex polyphilic molecules. [32][33][34][35] Molecular systems are readily coarse-grained to a DPD representation by replacing multi-atom chemical groups with simple, single-site microphase segregating groups (beads).…”
Section: Dpd Modelmentioning
confidence: 99%
“…Obviously, the stable morphologies for the cyclic-shaped RC copolymers are quite different from those of linear counterparts. The difference has been observed partly by our previous studies on the comparison between cyclic and linear RC melts [39] . The internal structure and rod arrangement within diverse aggregates will subsequently be discussed in detail.…”
Section: Effect Of Rod Length and Coil Lengthmentioning
confidence: 62%
“…Obviously, the architecture difference in RC molecule remarkably influences the self-assembly of aggregates. For cyclic RC copolymers, the rod is tethered by the coil with two junctions between rod and coil blocks, thus restricting the free degree of rod orientation and seriously influencing the aggregate behavior [39] . This finding is analogous to the study of Ouarti et al on coil-coil copolymer solubilized in selective solvent.…”
Section: Effect Of Rod Length and Coil Lengthmentioning
confidence: 99%
See 1 more Smart Citation